Curcumin Attenuates Ferroptosis-Induced Myocardial Injury in Diabetic Cardiomyopathy through the Nrf2 Pathway - Zhang Wei; Qian Shaohuan; Kang Pinfang; Shi Chao (Hindawi-Wiley, 2022)
Diabetes causes lipid peroxide to accumulate within cardiomyocytes. Furthermore, lipid peroxide buildup is a risk factor for ferroptosis. This study is aimed at examining whether curcumin can ameliorate ferroptosis in the treatment of diabetic cardiomyopathy. Hematoxylin and eosin and Masson sections were used to examine the morphology, arrangement, and degree of fibrosis of the myocardium of diabetic rabbit models. The expression levels of nuclear Nrf2, Gpx4, Cox1, and Acsl4 in diabetic animal and cell models were quantitatively analyzed using immunofluorescence and western blotting. Nrf2-overexpression lentivirus vectors were transfected into cardiomyocytes, and the protective effects of curcumin and Nrf2 on cardiomyocytes under high glucose stimulation were assessed using terminal deoxynucleotidyl transferase dUTP nick-end labelling and reactive oxygen species probes. Diabetes was found to disorder myocardial cell arrangement and significantly increase the degree of myocardial fibrosis and collagen expression in myocardial cells. Curcumin treatment can increase nuclear transfer of Nrf2 and the expression of Gpx4 and HO-1, reduce glucose induced myocardial cell damage, and reverse myocardial cell damage caused by the ferroptosis inducer erastin. This study confirmed that curcumin can promote the nuclear translocation of Nrf2, increase the expression of oxidative scavenging factors, such as HO-1, reduce excessive Gpx4 loss, and inhibit glucose-induced ferroptosis in cardiomyocytes. This highlights a potentially new therapeutic route for investigation for the treatment diabetic cardiomyopathy.